PENGEMBANGAN TES DIAGNOSTIK UNTUK MEMETAKAN MODEL MENTAL SISWA KELAS X SMA/MAN MATERI SUHU DAN KALOR - Amrizaldi Amrizaldi; Markus Diantoro; Wartono Wartono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
This research is the development of diagnostic tests to map the student‟s X grade models mental of SMA/MAN material temperature and heat. This research method Borg and Gall, namely (1) a preliminary study consisting of literature, field surveys, and development plans, (2) development of a draft product consisting of a draft product, due diligence, revised draft product, and product development results. Feasibility was measured by using due diligence by matter experts (lecturer of Physics and Teacher of Physics) and the audience (students). The results of the study in the form of quantitative and qualitative data. The data analysis technique used is the technique of analysis the average score. The results of the analysis of the average matter expert evaluators gained an average total of 3.55 which is in the category viable. Based on the analysis of data from the expert material, there are several items that need to be revised diagnostic tests. Based on the acquisition due diligence can be concluded that the diagnostic tests to map the student‟s X grade models mental of SMA/MAN material temperature and heat fit for use as a student assessment instruments.Keywords: Diagnostic Tests, Mental Models, Temperature Materials and Heat.